2009
DOI: 10.2310/6670.2009.00063
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Percutaneous Ultrasound-Accelerated Thrombolysis Versus Catheter-Directed Thrombolysis in Patients with Acute Massive Pulmonary Embolism

Abstract: Acute massive pulmonary embolism (PE) is a life-threatening condition that requires prompt and aggressive interventions, includinganticoagulation, catheter-directed thrombolysis (CDT), mechanical thrombectomy, or surgical thromboembolectomy. The aim of this study was to evaluate the treatment outcome in patients with massive PE who were treated with either ultrasound-accelerated thrombolysis using the EkoSonic Endovascular System (EKOS) or CDT intervention. During a recent 10-year period, the clinical records … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
94
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(103 citation statements)
references
References 56 publications
5
94
0
4
Order By: Relevance
“…Other studies showed the effect of endovascular sonolysis by the EkoSonic Endovascular System in patients with deep venous thrombosis of the lower extremities and in patients with pulmonary embolism. [30][31][32][33][34][35] Complete recanalization was achieved in 85.2%-96.0% of patients with arterial thrombosis 34,35 and in 83.0% patients with venous thrombosis. 31 Mahon et al 22 published the first experience with endovascular sonolysis by using the EkoSonic Endovascular System in patients with acute ischemic stroke.…”
Section: Discussionmentioning
confidence: 98%
“…Other studies showed the effect of endovascular sonolysis by the EkoSonic Endovascular System in patients with deep venous thrombosis of the lower extremities and in patients with pulmonary embolism. [30][31][32][33][34][35] Complete recanalization was achieved in 85.2%-96.0% of patients with arterial thrombosis 34,35 and in 83.0% patients with venous thrombosis. 31 Mahon et al 22 published the first experience with endovascular sonolysis by using the EkoSonic Endovascular System in patients with acute ischemic stroke.…”
Section: Discussionmentioning
confidence: 98%
“…One study showed an advantage of the EKOS system compared to catheter-directed thrombolysis alone in achieving thromboembolus removal in 100% of cases and reduction of removal time by approximately 8 hours (33). Moreover, the Ultrasound-Assisted Catheter Directed Thrombolysis for Acute Intermediate-Risk Pulmonary Embolism (ULTIMA) trial showed improvement in the right ventricular parameters without increased risk of death, major bleeding, or intracranial hemorrhage in submassive PE (9).…”
Section: Catheter-directed Thrombolysis Via Infusion Cathetersmentioning
confidence: 99%
“…22 Even shorter treatments of 17 hours with mean tPA doses of 0.86 mg/h effectively reduce the Miller score and result in larger thrombus resolution in comparison with higher rates and longer infusions via traditional, passive infusion catheters. 23 In a retrospective series of 24 patients with massive and submassive PE, a 12-hour treatment with the EKOS catheter infusing as little as 20 mg of tPA resulted in a statistically significant reduction in the RV to left ventricle ratio. 24 Early clinical experience has led to the approval of this device for treatment of PE in Europe where the ongoing randomized ULTrasound Accelerated ThrombolysIs of PulMonAry Embolism (ULTIMA) trial (ClinicalTrials.gov Identifier: NCT01166997) will compare outcomes in patients with submassive PE who are treated with the EKOS system versus standard anticoagulation.…”
Section: Ultrasound-assisted Therapiesmentioning
confidence: 99%